Yakitate!! Japan 4 - Hashiguchi, Takashi; Williams, Drew; Minami, Noritaka; Dutro, Steve (San Francisco, CA : VIZ Media, 2007)
"The Pantasia Rookie Tournament is in full swing with Kazuma going up against a daunting opponent in every respect--Tsukino's half-sister Mizuno and rival for control of the entire Pantasia chain! Mizuno is ready to knock Kazuma out of the ring with her super-tasty--and super-expensive to make--patented melon bread. Can Kazuma compete against this high-class recipe with a can of regular old melon juice? Plus, some exciting bonus info on the origins of Ken Matsushiro, the afro-sporting manager of the Pantasia South Branch!"--P. [4] of cover.
In keeping with the original format, this book reads from back to front and from right to left.
Keywords: Teenage boys -- Japan; Bakers -- Japan; Comic books, strips, etc. -- Japan; Graphic novels